Diversity in the Bean Nodulating Rhizobial Population of North West of Argentina - Aguilar, Orlando Mario (2000)
The southern Andes in Argentina is considered to be part of the South American centre of bean domestication. The other centre of origin took place in Mesoamerica. In the NWA region it is possible to find the wild bean Phaseolus vulgaris var. aborigineus , the ancestors of bean cultivated bean varieties, growing in virgin lands, therefore it is an interesting ecosystem to assess whether the wild bean variety had developed specificity that ended in some particular host-rhizobium association. Another interesting feature of NWA is that the Argentinian bean production resulting of 245,000 Ha of cultivated beans is generated in this region. It had been demonstrated that P. vulgaris is a permissive host, and that several species have been distinguished and new species have been recently described for strains recovered from nodules collected at different sites from all over the world. The majoritiy of isolates from nitrogen fixing nodules of P. vulgaris in Mesoamerica are R.etli, whereas R.tropici have also been isolated from diverse South American regions such as Brazil, Colombia and also in France and Kenyan acid soils. Two additional species R.gallicum and R.giardinii have been described. It seems important to gain more information on the occurrence of Rhizobium species that nodulate beans in different locations of the NWA. We examined a collection of rhizobial isolates from wild beans growing in virgin lands, and rhizobia that were retrieved from soil in laboratory using common beans and leucaena as the trapping hosts, by using analysis of chormosomal DNA markers such as RFLP-16S rDNA and rep-fingerprinting, and of symbiotic plasmid markers such as RFLP of nodC and nif H.